Highly Sensitive Hydrazine Chemical Sensor Based on CNT-PdPt Nanocomposites - Sung Phil Kim (Journal of Nanomaterials, 2015)
Bimetallic PdPt nanoparticles were prepared using the chemical reduction method. The PdPt nanoparticles were successfully deposited on thiolated carbon nanotubes (CNTs) to form a CNT-PdPt nanocomposite as an electron mediator for the fabrication of a hydrazine sensor. The PdPt nanoparticles had an average particle size of 2.3 nm and were well dispersed on the surfaces of the CNTs in the prepared CNT-PdPt nanocomposite, as demonstrated using transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDX), and X-ray diffraction (XRD). Based on X-ray photoelectron spectroscopy (XPS) results, the estimated proportions of Pd and Pt in the CNT-PdPt nanocomposite were approximately 3.0% and 3.2%, respectively. A fabricated chemical sensor based on CNT-PdPt was found to exhibit better amperometric activity with respect to the hydrazine oxidation reaction than CNT-Pd, CNT-Pt, and commercial Pd/C and Pt/C catalysts. This sensor exhibited a linear range of 0.55–1,200 μM and a detection limit of 0.28 μM (S/N = 3) with a fast response time (within 5 s). Furthermore, the sensor could be used repeatedly for the consecutive detection of hydrazine with good reusability and storage stability. These properties demonstrate that the CNT-PdPt nanocomposite is a promising electron mediator for the fabrication of amperometric hydrazine sensors.